Adhesion of annexin 7 deficient erythrocytes to endothelial cells. - Majed Abed (Public Library of Science (PLoS), 2013)
Annexin 7 deficiency has previously been shown to foster suicidal death of erythrocytes or eryptosis, which is triggered by increase of intracellular Ca(2+) concentration ([Ca(2+)](i)) and characterized by cell shrinkage and cell membrane scrambling with subsequent phosphatidylserine exposure at the cell surface. Eryptosis following increase of [Ca(2+)](i) by Ca(2+) ionophore ionomycin, osmotic shock or energy depletion was more pronounced in erythrocytes from annexinA7-deficient mice (anxA7(-/-)) than in erythrocytes from wild type mice (anxA7(+/+)). As phosphatidylserine exposure is considered to mediate adhesion of erythrocytes to the vascular wall, the present study explored adhesion of erythrocytes from anx7(-/-) and anx7(+/+)-mice following increase of [Ca(2+)](i) by Ca(2+) ionophore ionomycin (1 µM for 30 min), hyperosmotic shock (addition of 550 mM sucrose for 2 hours) or energy depletion (removal of glucose for 12 hours). Phosphatidylserine exposing erythrocytes were identified by annexin V binding, cell volume estimated from forward scatter in FACS analysis and adhesion to human umbilical vein endothelial cells (HUVEC) utilizing a flow chamber. As a result, ionomycin, sucrose addition and glucose removal all triggered phosphatidylserine-exposure, decreased forward scatter and enhanced adhesion of erythrocytes to human umbilical vein endothelial cells (HUVEC), effects significantly more pronounced in anx7(-/-) than in anx7(+/+)-erythrocytes. Following ischemia, morphological renal injury was significantly higher in anx7(-/-) than in anx7(+/+)-mice. The present observations demonstrate that enhanced eryptosis of annexin7 deficient cells is paralleled by increased adhesion of erythrocytes to the vascular wall, an effect, which may impact on microcirculation during ischemia.